Polymer fiber membrane with selective catalytic self-degradation function as well as preparation method and application thereof
By adding a core-shell photocatalyst with pH selectivity to the polymer fiber membrane, the contradiction between stability and rapid degradability of existing materials during use is solved, and the effect of stable use under conventional environments and rapid degradation under specific conditions is achieved.
Patent Information
- Application Number
- CN202510185508.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-20
AI Technical Summary
It is difficult for existing degradable materials to maintain stability during use and to rapidly degrade under specific conditions, making it difficult to achieve both stability and rapid degradability of materials.
The shell is prepared by controlling the synthetic conditions of Al2O3, and a core-shell-type photocatalyst with pH selectivity was obtained, which was added to the polymer fiber membrane to prepare a polymer fiber membrane with self-degradation function.
It achieves stability under conventional use environment and rapid photodegradation under specific pH conditions. During the degradation process, intermediate products are non-toxic to the environment and are environmentally selective.
Smart Images

Figure CN119800611A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of degradable polymer fibers, and in particular to a polymer fiber membrane with a selective catalytic self-degradation function, and a preparation method and application thereof. Background Art
[0002] In recent years, microplastic pollution has become one of the most serious environmental problems in the world. Among the many types of microplastics, fibers account for the largest proportion. Therefore, solving the problem of waste fiber pollution has become one of the most urgent issues. Degradable materials have always been considered as alternatives to traditional non-degradable materials and one of the most effective ways to solve the problem of plastic pollution.
[0003] At present, the most widely used degradable materials in the market are still biodegradable materials, but the degradation conditions of biodegradable materials are harsh, and the degradation performance is affected by too many environmental factors, such as the type of microorganisms, the distribution of microorganisms, humidity, pH, etc., and the required degradation time is too long, at least several months. Therefore, degradable materials with simple degradation conditions, fast degradation rate and no impact on normal use are more attractive for alleviating plastic pollution.
[0004] The degradation conditions of photodegradable materials are simple, the main energy source is sunlight, the conditions are mild, and the environment is highly universal. Photodegradable materials are divided into two types: synthetic and additive. The production process of synthetic photodegradable materials is relatively complicated, and often requires complex metal complexes as catalysts. In contrast, the preparation conditions of additive photodegradable materials are simple. It only requires adding photosensitizers with photocatalytic activity to the polymer to give the material the ability to photodegrade.
[0005] Additive photodegradable materials have a faster degradation rate. Patent CN201510801124.4 reported that adding a photodegradation agent to PE can give PE the ability to photodegrade, and the material can be fully degraded in a short time under light. Patent CN01128331.9 mentioned that adding the photosensitizer ferric citrate to PP resin can degrade the PP resin material into powder within 75 days. However, the biggest problem with additive photodegradable materials is that it is difficult to simultaneously achieve the stability of the material during use and the rapid degradation after becoming waste. Therefore, it is extremely important to develop photodegradable materials that have good stability under conventional use environments and good degradability under specific conditions. Summary of the invention
[0006] The purpose of the present invention is to provide a polymer fiber membrane with selective catalytic self-degradation function and its preparation method and application. The shell is prepared by controlling the synthesis conditions of Al2O3 to obtain a core-shell photocatalyst with pH selectivity, which is added to the polymer fiber membrane to prepare a polymer fiber membrane with self-degradation function.
[0007] To achieve the above object, the present invention provides a method for preparing a polymer fiber membrane with a selective catalytic self-degradation function, comprising the following steps:
[0008] S1. Dissolving the dispersant in deionized water, adding the nano-photocatalyst, and performing ultrasonic homogenization followed by magnetic stirring to obtain a photocatalyst dispersion;
[0009] S2, dissolving aluminum salt in deionized water to obtain an aluminum salt solution;
[0010] S3, under magnetic stirring, slowly dropwise add the aluminum salt solution obtained in S2 to the photocatalyst dispersion in S1 to obtain a mixed system, adjust the pH of the mixed system to 5-12, age after stirring, wash and dry to obtain a core-shell photocatalyst;
[0011] S4, dissolving the polymer to obtain a polymer solution, adding the core-shell photocatalyst obtained in S3, and stirring evenly at 20-40° C. to obtain a polymer spinning solution;
[0012] S5. Spin the polymer spinning solution in S4 using a centrifugal-electrospinning method, and dry it to obtain a polymer fiber membrane.
[0013] Preferably, in S1, the dispersant is (NaPO3)6, and the nano-photocatalyst includes one or more of WO3, CdS, BiVO4, TiO2, SrTiO3, ZnO, and CuO.
[0014] Preferably, in S2, the aluminum salt is NaAlO2.
[0015] Preferably, in S3, the mass of the aluminum salt is 0.5-5.0% of the total mass of the mixed system, the mass of the dispersant is 0.01-0.05% of the total mass of the mixed system, the stirring temperature is 20-80°C, the aging time is 24-48h, and the drying temperature is 60-180°C.
[0016] Preferably, in S4, the polymer is one or more of polymer chips and polymer powder;
[0017] The polymer includes one or more of polyethylene terephthalate (PET), polyacrylonitrile (PAN), polyethylene (PE), polypropylene (PP), polycarbonate (PC), polyvinyl chloride (PVC), polystyrene (PS), and polyamide (PA).
[0018] Preferably, in S4, the concentration of the polymer solution is 5-15 wt %, and the dissolution temperature of the polymer is 20-40°C.
[0019] Preferably, in S4, the amount of the core-shell photocatalyst added to the polymer spinning solution is 0.5-5 wt %.
[0020] Preferably, in S5, the spinning parameters of the centrifugal-electrospinning method include: the spinning needle is one of 25G, 27G and 30G, the spinning speed is 3500r / min, the voltage is 10kV, and the collection distance is 10cm.
[0021] The polymer fiber membrane prepared by the above method for preparing a polymer fiber membrane with selective catalytic self-degradation function.
[0022] The above-mentioned application of the polymer fiber membrane with selective catalytic self-degradation function is applied in the preparation of clothing, carpets, curtains and toys.
[0023] The mechanism of the present invention is:
[0024] Under neutral, alkaline and weakly acidic conditions, the Al2O3 on the surface of the core-shell photocatalyst has good stability, can shield light, protect the internal nano-photocatalyst particles from being excited, and allow the polymer fiber membrane to be used normally. Under pH 3 conditions, the Al2O3 shell of the core-shell photocatalyst dissolves and falls off, exposing the internal nano-photocatalyst particles, which produce ·OH and ·O2 - , 1 O2 and other free radicals, thereby oxidizing the nearby polymer chains to achieve the purpose of self-degradation.
[0025] Therefore, the present invention adopts the above-mentioned polymer fiber membrane with selective catalytic self-degradation function and its preparation method and application, and its beneficial effects are:
[0026] 1. The present invention controls the synthesis conditions of Al2O3 to prepare a shell, obtains a core-shell photocatalyst with pH selectivity, and adds it to a polymer fiber to prepare a photodegradable polymer fiber membrane with environmental selectivity;
[0027] 2. The polymer fiber membrane prepared in the present invention has pH selectivity and can be fully degraded after being irradiated by sunlight. The intermediate products produced during the degradation process are non-toxic to the environment, which can ensure normal storage and use under conventional conditions. When the polymer fiber membrane becomes waste, it can be rapidly photodegraded under specific conditions, achieving the coexistence of usability and degradability.
[0028] 3. The content of the core-shell photocatalyst added to the polymer fiber membrane in the present invention is relatively low, which can improve the tensile strength of the polymer fiber membrane, and the elongation at break only decreases slightly, which has little effect on the mechanical properties of the polymer fiber membrane.
[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a SEM image of the original TiO2 and the core-shell photocatalyst TiO2@Al2O3 in Example 1 of the present invention;
[0031] Figure 2 is a schematic diagram of the polymer fiber membrane TiO2@Al2O3 / PA6 in Example 1 of the present invention;
[0032] Figure 3 is a photodegradation performance diagram of the polymer fiber membrane under different pH conditions in Example 1 of the present invention;
[0033] Figure 4 is a composite diagram showing the change of the actual morphology of the polymer fiber membrane with the illumination time when the pH value of the polymer fiber membrane in Example 1 of the present invention is 3;
[0034] Figure 5 is a graph showing the mass loss of the polymer fiber membrane in Example 2 of the present invention after irradiation for 100 hours under different pH conditions;
[0035] Figure 6 3 is a SEM image of the polymer fiber membrane before and after irradiation in Example 3 of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0037] Example 1
[0038] S1. Dissolve 4 mg of dispersant (NaPO3)6 in 10 mL of deionized water, add 1 g of nano-photocatalyst TiO2, ultrasonicate for 10 min until uniform, and then magnetically stir for 1.5 h to obtain a photocatalyst dispersion.
[0039] S2. Dissolve 156 mg of aluminum salt NaAlO2 in 2 mL of deionized water to obtain an aluminum salt solution.
[0040] S3, under magnetic stirring at 30°C, slowly drop the aluminum salt solution obtained in S2 into the photocatalyst dispersion in S1 to obtain a mixed system, add dilute sulfuric acid in parallel to adjust the pH of the mixed system to 7, stir at 30°C for 1.5h and then age for 40h, wash with deionized water to remove excess aluminum salt, dry at 150°C for 24h to obtain a core-shell photocatalyst TiO2@Al2O3, such as Figure 1 As shown, Figure 1(a) is the SEM image of the original TiO2, showing that the edge of the nano-photocatalyst TiO2 particles is clear and the diameter is about 25nm. Figure 1 (b) is the SEM image of the core-shell photocatalyst TiO2@Al2O3. It can be seen that a layer of Al2O3 film is obviously formed on the surface of the nanophotocatalyst. The nanophotocatalyst particles are core-shell in shape, and the diameter increases to about 40nm, which is enough to show that this method has successfully prepared the core-shell catalyst TiO2@Al2O3.
[0041] S4. Dissolve 1.75 g of polyamide 6 (PA6) in 10 mL of hexafluoroisopropanol (HFIP) under stirring at 35°C for 12 h to obtain a polymer solution, add 44.4 mg of the core-shell photocatalyst obtained in S3 (the core-shell catalyst accounts for 2.5 wt% of the total mass (core-shell catalyst + polymer)), and stir at 35°C for 24 h to obtain a polymer spinning solution.
[0042] S5, using centrifugal-electrospinning method to spin the polymer spinning solution in S4, the spinning parameters include: spinning needle is 27G, spinning speed is 3500r / min, voltage is 10kV, collection distance is 10cm. Drying at 60℃ for 12h to remove excess solvent, to obtain polymer fiber membrane TiO2@Al2O3 / PA6, such as Figure 2 shown.
[0043] Example 2
[0044] S1. Dissolve 4 mg of dispersant (NaPO3)6 in 10 mL of deionized water, add 1 g of nano-photocatalyst TiO2, ultrasonicate for 10 min until uniform, and then magnetically stir for 1.5 h to obtain a photocatalyst dispersion.
[0045] S2. Dissolve 78 mg of aluminum salt NaAlO2 in 2 mL of deionized water to obtain an aluminum salt solution.
[0046] S3. Under magnetic stirring at 50°C, the aluminum salt solution obtained in S2 is slowly added dropwise to the photocatalyst dispersion in S1 to obtain a mixed system. Dilute sulfuric acid is added dropwise by the parallel flow method to adjust the pH of the mixed system to 7. The system is stirred at 50°C for 1.5h and aged for 36h. Excess aluminum salt is removed by washing with deionized water and dried at 150°C for 24h to obtain a core-shell photocatalyst TiO2@Al2O3.
[0047] S4. Dissolve ethylene terephthalate (PET) in HFIP under stirring at 35°C for 12 h to obtain a 12 wt% polymer solution, add the core-shell photocatalyst obtained in S3 (the core-shell catalyst accounts for 2.5 wt% of the total mass (core-shell catalyst + polymer)), and stir at 35°C for 24 h to obtain a polymer spinning solution.
[0048] S5, spinning the polymer spinning solution in S4 by centrifugal-electrospinning method, the spinning parameters include: spinning needle is 25G, spinning speed is 3500r / min, voltage is 10kV, collection distance is 10cm. Drying at 60℃ for 12h to remove excess solvent, to obtain polymer fiber membrane TiO2@Al2O3 / PET.
[0049] Example 3
[0050] S1. Dissolve 6 mg of dispersant (NaPO3)6 in 10 mL of deionized water, add 1 g of nano-photocatalyst ZnO, ultrasonicate for 10 min until uniform, and then magnetically stir for 1.5 h to obtain a photocatalyst dispersion.
[0051] S2. Dissolve 234 mg of aluminum salt NaAlO2 in 3 mL of deionized water to obtain an aluminum salt solution.
[0052] S3. Under magnetic stirring at 80°C, the aluminum salt solution obtained in S2 is slowly added dropwise to the photocatalyst dispersion in S1 to obtain a mixed system. Dilute sulfuric acid is added dropwise by the parallel flow method to adjust the pH of the mixed system to 9. The system is stirred at 80°C for 1.5 hours and then aged for 40 hours. The excess aluminum salt is washed with deionized water and dried at 150°C for 24 hours to obtain a core-shell photocatalyst ZnO@Al2O3.
[0053] S4. Dissolve polyacrylonitrile (PAN) in 10 mL of N,N-dimethylformamide (DMF) under stirring at 35°C for 12 h to obtain a 10 wt% polymer solution, add the core-shell photocatalyst obtained in S3 (the core-shell catalyst accounts for 5.0 wt% of the total mass (core-shell catalyst + polymer)), and stir at 35°C for 24 h to obtain a polymer spinning solution.
[0054] S5, spinning the polymer spinning solution in S4 by centrifugal-electrospinning method, the spinning parameters include: spinning needle is 30G, spinning speed is 3500r / min, voltage is 10kV, collection distance is 10cm. Drying at 60℃ for 12h to remove excess solvent, to obtain polymer fiber membrane ZnO@Al2O3 / PAN.
[0055] Example 4
[0056] S1. Dissolve 4 mg of dispersant (NaPO3)6 in 10 mL of deionized water, add 1 g of nano-photocatalyst CdS, ultrasonicate for 10 min until uniform, and then magnetically stir for 1.5 h to obtain a photocatalyst dispersion.
[0057] S2. Dissolve 200 mg of aluminum salt NaAlO2 in 3 mL of deionized water to obtain an aluminum salt solution.
[0058] S3. Under magnetic stirring at 80°C, the aluminum salt solution obtained in S2 is slowly added dropwise to the photocatalyst dispersion in S1 to obtain a mixed system. Dilute sulfuric acid is added dropwise by the parallel flow method to adjust the pH of the mixed system to 11.5. The system is stirred at 80°C for 1.5 hours and then aged for 40 hours. The excess aluminum salt is washed with deionized water and dried at 150°C for 24 hours to obtain a core-shell photocatalyst CdS@Al2O3.
[0059] S4. Dissolve PAN in DMF under stirring at 35°C for 12 h to obtain a 10 wt% polymer solution, add the core-shell photocatalyst obtained in S3 (the core-shell catalyst accounts for 5.0 wt% of the total mass (core-shell catalyst + polymer)), and stir at 35°C for 24 h to obtain a polymer spinning solution.
[0060] S5, spinning the polymer spinning solution in S4 by centrifugal-electrospinning method, the spinning parameters include: spinning needle is 30G, spinning speed is 3500r / min, voltage is 10kV, collection distance is 10cm. Drying at 60℃ for 12h to remove excess solvent, to obtain polymer fiber membrane CdS@Al2O3 / PAN.
[0061] Comparative Example 1
[0062] S1. Dissolve 5 mg of dispersant (NaPO3)6 in 10 mL of deionized water, add 1 g of nano-photocatalyst TiO2, ultrasonicate for 10 min until uniform, and then magnetically stir for 1.5 h to obtain a photocatalyst dispersion.
[0063] S2. Dissolve 39 mg of aluminum salt NaAlO2 in 2 mL of deionized water to obtain an aluminum salt solution.
[0064] S3. Under magnetic stirring at 30°C, the aluminum salt solution obtained in S2 is slowly added dropwise to the photocatalyst dispersion in S1 to obtain a mixed system. Dilute sulfuric acid is added dropwise by the parallel flow method to adjust the pH of the mixed system to 9. The mixture is stirred at 80°C for 1.5h and aged for 24h. Excess aluminum salt is washed with deionized water and dried at 100°C for 24h to obtain the photocatalyst TiO2@Al2O3.
[0065] S4. Dissolve PA6 in HFIP under stirring at 35°C for 12h to obtain a 10wt% polymer solution, add the photocatalyst obtained in S3 (the core-shell catalyst accounts for 2.0wt% of the total mass (core-shell catalyst + polymer)), and stir at 35°C for 24h to obtain a polymer spinning solution.
[0066] S5, spinning the polymer spinning solution in S4 by centrifugal-electrospinning method, the spinning parameters include: spinning needle is 27G, spinning speed is 3500r / min, voltage is 10kV, collection distance is 12cm. Drying at 60℃ for 12h to remove excess solvent, and obtain polymer fiber membrane TiO2@Al2O3 / PA6.
[0067] Comparative Example 2
[0068] S1. Dissolve 5 mg of dispersant (NaPO3)6 in 10 mL of deionized water, add 1 g of nano-photocatalyst TiO2, ultrasonicate for 10 min until uniform, and then magnetically stir for 1.5 h to obtain a photocatalyst dispersion.
[0069] S2. Dissolve 312 mg of aluminum salt NaAlO2 in 4 mL of deionized water to obtain an aluminum salt solution.
[0070] S3. Under magnetic stirring at 80°C, the aluminum salt solution obtained in S2 is slowly added dropwise to the photocatalyst dispersion in S1 to obtain a mixed system. Dilute sulfuric acid is added dropwise by the parallel flow method to adjust the pH of the mixed system to 9. The mixture is stirred at 80°C for 1.5 hours and then aged for 24 hours. The excess aluminum salt is washed with deionized water and dried at 100°C for 24 hours to obtain the photocatalyst TiO2@Al2O3.
[0071] S4. Dissolve PA6 in HFIP under stirring at 35°C for 12h to obtain a 10wt% polymer solution, add the photocatalyst obtained in S3 (core-shell catalyst accounts for 25wt% of the total mass (core-shell catalyst + polymer)), and stir at 35°C for 24h to obtain a polymer spinning solution.
[0072] S5, spinning the polymer spinning solution in S4 by centrifugal-electrospinning method, the spinning parameters include: spinning needle is 27G, spinning speed is 3500r / min, voltage is 10kV, collection distance is 12cm. Drying at 60℃ for 12h to remove excess solvent, and obtain polymer fiber membrane TiO2@Al2O3 / PA6.
[0073] Comparative Example 3
[0074] S1. Dissolve 4 mg of dispersant (NaPO3)6 in 10 mL of deionized water, add 1 g of nano-photocatalyst WO3, ultrasonicate for 10 min until uniform, and then magnetically stir for 1.5 h to obtain a photocatalyst dispersion.
[0075] S2. Dissolve 200 mg of aluminum salt NaAlO2 in 2.5 mL of deionized water to obtain an aluminum salt solution.
[0076] S3. Under magnetic stirring at 60°C, the aluminum salt solution obtained in S2 is slowly added dropwise to the photocatalyst dispersion in S1 to obtain a mixed system. Dilute sulfuric acid is added dropwise by the parallel flow method to adjust the pH of the mixed system to 8. The mixture is stirred at 60°C for 1.5 hours and aged for 24 hours. The excess aluminum salt is washed with deionized water and dried at 80°C for 24 hours to obtain the photocatalyst WO3@Al2O3.
[0077] S4. Dissolve polystyrene (PS) in DMF under stirring at 35°C for 12 h to obtain a 9 wt% polymer solution, add the photocatalyst obtained in S3 (the core-shell catalyst accounts for 1.0 wt% of the total mass (core-shell catalyst + polymer)), and stir at 35°C for 24 h to obtain a polymer spinning solution.
[0078] S5, spinning the polymer spinning solution in S4 by centrifugal-electrospinning method, the spinning parameters include: spinning needle is 27G, spinning speed is 3500r / min, voltage is 10kV, collection distance is 12cm. Drying at 60℃ for 12h to remove excess solvent, to obtain polymer fiber membrane WO3@Al2O3 / PS.
[0079] Test Example 1
[0080] The polymer fiber membranes obtained in Examples 1-4 and Comparative Examples 1-3 were placed in aqueous solutions with pH values of 3, 5, 7, 9, and 11 for simulated light exposure, and the self-degradation of the polymer fiber membranes under acidic, neutral, and alkaline conditions was tested, as shown in Table 1.
[0081] Table 1. Degradation of polymer fiber membranes in Examples 1-4 and Comparative Examples 1-3
[0082]
[0083] It can be seen from Table 1 that the polymer fiber membranes in Examples 1-4 have pH selectivity, self-degrading at a pH of 3, and not degrading under neutral, alkaline and weakly acidic conditions. Figure 3 It can be seen that the polymer fiber membrane in Example 1 can achieve a mass loss of 38% after 120 hours of sunlight irradiation at a pH of 3, and almost no degradation occurs under neutral, alkaline and weakly acidic conditions. Figure 4 It can be seen that Figure 4 (a)-(f) represent the macroscopic morphologies after irradiation for 0 h, 24 h, 48 h, 72 h, 96 h and 120 h, respectively. The polymer fiber membrane in Example 1 gradually degrades with the increase of irradiation time, and finally only a small amount of powder remains.
[0084] Depend on Figure 5It can be seen that the polymer fiber membrane in Example 2 undergoes photodegradation at pH 3, and can achieve a mass loss of 11.1% after only 100 h of sunlight irradiation, while it is stable under neutral, alkaline and weakly acidic conditions. Figure 6 It can be seen that the polymer fiber membrane in Example 3 before illumination ( Figure 6 (a) in the figure shows a complete fiber morphology. After 150 hours of light exposure, ( Figure 6 In (b), the fiber was obviously broken and a large number of holes appeared on the surface, confirming the self-degradation property of the polymer fiber membrane matrix. The polymer fiber membrane in Example 4 lost about 25% of its mass after 150 hours of simulated light exposure at pH 3, but did not degrade under neutral, alkaline and weakly acidic conditions.
[0085] The polymer fiber membrane in Comparative Example 1 has weak self-degradation performance under acidic, neutral and alkaline conditions, and the degradation performance of the polymer fiber membrane is not pH selective because under the preparation conditions, Al2O3 does not form a coating on TiO2, and only exists in the form of Al2O3 particles.
[0086] The polymer fiber membrane in Comparative Example 2 can be self-degraded under acidic, neutral and alkaline conditions, and the degradation performance of the polymer fiber membrane is not pH selective because under the preparation conditions, Al2O3 does not form a coating on TiO2, but only exists in the form of Al2O3 particles.
[0087] In Comparative Example 3, the polymer fiber membrane is difficult to self-degrade under acidic, neutral and alkaline conditions, and the degradation performance of the polymer fiber membrane is not pH selective. 3+ It is difficult to adsorb on the catalyst surface, so it is difficult to form a coating. The prepared Al2O3 is easy to form blocky particles, which have a shielding effect on light.
[0088] Therefore, the present invention adopts the above-mentioned polymer fiber membrane with selective catalytic self-degradation function and its preparation method and application, prepares the shell by controlling the synthesis conditions of Al2O3, obtains a core-shell photocatalyst with pH selectivity, and adds it to the polymer fiber to prepare a photodegradable polymer fiber membrane with environmental selectivity.
[0089] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a polymer fiber membrane with selective catalytic self-degradation function, characterized in that: The following steps are included: S1. Dissolving the dispersant in deionized water, adding the nano-photocatalyst, and performing ultrasonic homogenization followed by magnetic stirring to obtain a photocatalyst dispersion; S2, dissolving aluminum salt in deionized water to obtain an aluminum salt solution; S3, under magnetic stirring, slowly dropwise add the aluminum salt solution obtained in S2 to the photocatalyst dispersion in S1 to obtain a mixed system, adjust the pH of the mixed system to 5-12, age after stirring, wash and dry to obtain a core-shell photocatalyst; S4, dissolving the polymer to obtain a polymer solution, adding the core-shell photocatalyst obtained in S3, and stirring evenly at 20-40° C. to obtain a polymer spinning solution; S5. Spin the polymer spinning solution in S4 using a centrifugal-electrospinning method, and dry it to obtain a polymer fiber membrane.
2. The method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to claim 1, characterized in that: In S1, the dispersant is (NaPO3)6, and the nano-photocatalyst includes one or more of WO3, CdS, BiVO4, TiO2, SrTiO3, ZnO, and CuO.
3. The method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to claim 1, characterized in that: In S2, the aluminum salt is NaAlO2.
4. The method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to claim 1, characterized in that: In S3, the mass of the aluminum salt is 0.5-5.0% of the total mass of the mixed system, the mass of the dispersant is 0.01-0.05% of the total mass of the mixed system, the stirring temperature is 20-80°C, the aging time is 24-48h, and the drying temperature is 60-180°C.
5. The method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to claim 1, characterized in that: In S4, the polymer is one or more of polymer chips and polymer powder; The polymer includes one or more of polyethylene terephthalate, polyacrylonitrile, polyethylene, polypropylene, polycarbonate, polyvinyl chloride, polystyrene, and polyamide.
6. The method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to claim 1, characterized in that: In S4, the concentration of the polymer solution is 5-15 wt %, and the dissolution temperature of the polymer is 20-40°C.
7. The method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to claim 1, characterized in that: In S4, the amount of the core-shell photocatalyst added to the polymer spinning solution is 0.5-5 wt%.
8. The method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to claim 1, characterized in that: In S5, the spinning parameters of the centrifugal-electrospinning method include: the spinning needle is one of 25G, 27G and 30G, the spinning speed is 3500r / min, the voltage is 10kV, and the collection distance is 10cm.
9. The polymer fiber membrane prepared according to the method for preparing a polymer fiber membrane with selective catalytic self-degradation function according to any one of claims 1 to 8.
10. The use of a polymer fiber membrane with selective catalytic self-degradation function according to claim 9, characterized in that: Polymer fiber films are used in the preparation of clothing, carpets, curtains and toys.
Citation Information
Patent Citations
Composite porous fibers with core-shell structures and preparation method of dual-pore structure membrane
CN103572606A
Flexible titanium oxide nanofiber membrane and preparation method thereof
CN104153123A
Polypyrrole chitosan drug-loaded fibrous membrane for artificial nerve conduit and preparation method of polypyrrole chitosan drug-loading fibrous membrane
CN112962220A
Method for preparing nano-composite antibacterial fiber membrane based on electrostatic spinning technology
CN113604962A
Flexible polycrystalline titanium oxide-aluminum oxide composite nanofiber membrane and preparation method thereof
CN114045608A